Axillary lymph node response to neoadjuvant systemic therapy with dedicated axillary hybrid 18F-FDG PET/MRI in clinically node-positive breast cancer patients: a pilot study. Issue 10 (October 2022) - de Mooij, C.M.; Samiei, S.; Mitea, C.; Lobbes, M.B.I.; Kooreman, L.F.S.; Heuts, E.M.; Beets-Tan, R.G.H.; van Nijnatten, T.J.A.; Smidt, M.L.
Abstract : AIM: To investigate the diagnostic performance of dedicated axillary hybrid 18 F-2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG) positron emission tomography (PET)/magnetic resonance imaging (MRI) in detecting axillary pathological complete response (pCR) following neoadjuvant systemic therapy (NST) in clinically node-positive breast cancer patients. MATERIALS AND METHODS: Ten prospectively included clinically node-positive breast cancer patients underwent dedicated axillary hybrid 18 F-FDG PET/MRI after completing NST followed by axillary surgery. PET images were reviewed by a nuclear medicine physician and coronal T1-weighted and T2-weighted MRI images by a radiologist. All axillary lymph nodes visible on PET/MRI were matched with those removed during axillary surgery. Diagnostic performance parameters were calculated based on patient-by-patient and node-by-node validation with histopathology of the axillary surgical specimen as the reference standard. RESULTS: Six patients achieved axillary pCR at final histopathology. A total of 84 surgically harvested axillary lymph nodes were matched with axillary lymph nodes depicted on PET/MRI. Histopathological examination of the matched axillary lymph nodes resulted in 10 lymph nodes with residual axillary disease of which eight contained macrometastases and two micrometastases. The patient-by-patient analysis yielded a sensitivity, specificity, positive predictive value, and negative predictive value of 25%, 100%, 100%, and 67%, respectively. The diagnostic performance parameters of the node-by-node analysis were 0%, 96%, 0%, and 88%, respectively. Excluding micrometastases from the node-by-node analysis increased the negative predictive value to 90%. CONCLUSION: This pilot study suggests that the negative predictive value and sensitivity of dedicated axillary 18 F-FDG PET/MRI are insufficiently accurate to detect axillary pCR or exclude residual axillary disease following NST in clinically node-positive breast cancer patients. Highlights: Dedicated axillary PETMRI for axillary pCR detection in node-positive breast cancer. Limited diagnostic accuracy of axillary PETMRI for axillary pCR following NST. Metabolic dissolution of SUVmax does not accurately reflect axillary pCR after NST.